Techniques and Evaluation Tests for Colon Cancer Treatment Using Pellets: A Review - Shubham M. Waghmare; Namrata N. More; Suraj R. Jagtap; Trushali A. Mandhare; Gaurav K. Soni; Ajay Y. Kale (Current Research in Pharmaceutical Sciences, 2024)
This review outlines the manufacturing process for globular pellets. The production method includes the following steps: drug stacking, displacement-merumerization, cryopelletization, shrink, balling, hot-soften extrusion generation, freeze pelletization, spray-drying, and spray-congealing. The benefits and risks of several pelletization methods were discussed. The current study’s objective is to examine the efficacy of anticancer drugs and metal chelators in treating colorectal cancer (CRC). Phytic acid, 5-fluorouracil (5-FU), microcrystalline cellulose (MCC) PH 100 and 1 compile in the pellets, hydroxypropyl methylcellulose (HPMC), and barium sulphate were processed utilizing the extrusion spheronization technology. To achieve colon-specific medication delivery, Eudragit S100 was layered over the ability pellets. Pellets have been praised for a variety of micromeritic and medicinal qualities. In the Ehrlich ascites carcinoma (EAC)-driven patient-derived zenograft (PDX) paradigm, the in vivo treatment potency separates the pharmacokinetic and pharmacodynamic bounds. By chelating manganese, phytic acid, and five-FU combinations, they appear to provide more cytotoxic interest through a better reactive oxygen species (ROS) stage. Later pharmacokinetic studies showed a maximum 50% drop in Cmax within the finished setup, indicating decreased inherent exposure to the drug component.